UTILIZATION OF ARABICA COFFEE WASTE (coffea arabica) AS AN ADDITIVE IN THE PRODUCTION OF AROMATHERAPY CANDLES (scanted candle) USING PARAFFIN AND STEARIC ACID AS RAW MATERIALS - Auliza, Wulan (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACTAromatherapy candles are an alternative application of aromatherapy through inhalation, producing aromas that provide therapeutic effects when burned. They serve as alternative medicine, decoration, and room fragrance. The purpose of creating aromatherapy candles is to enhance home decor while supporting a healthy living aroma through the therapeutic process. This research was conducted to formulate and test the physical properties of aromatherapy candles using a combination of stearic acid and additives (coffee). Natural materials that can be used for making aromatherapy candles include coffee grounds. Physical property tests were carried out, including organoleptic tests, burn time tests, flame height tests, and melting point tests. The best research result for stearic acid was 6 grams in sample 1 with 30 grams of coffee grounds. The best result for flame height was 2 grams in sample 1 with 10 grams of coffee grounds, and the best melting point result was 30 grams of coffee grounds with a melting point of 50-58°C. This research was conducted according to the SNI standard for aromatherapy candles. Keywords: Aromatherapy Candles, Essential Oil, Paraffin, Stearic Acid